Novel strategies in Parkinson’s disease treatment: a review - Mitchell, Charles L.; Kurouski, Dmitry (Frontiers in Molecular Neuroscience, 2024)
An unprecedented extension of life expectancy observed during the past century drastically increased the number of patients diagnosed with Parkinson’s diseases (PD) worldwide. Estimated costs of PD alone reached 52 billion per year, making effective neuroprotective treatments an urgent and unmet need. Current treatments of both AD and PD focus on mitigating the symptoms associated with these pathologies and are not neuroprotective. In this review, we discuss the most advanced therapeutic strategies that can be used to treat PD. We also critically review the shift of the therapeutic paradigm from a small molecule-based inhibition of protein aggregation to the utilization of natural degradation pathways and immune cells that are capable of degrading toxic amyloid deposits in the brain of PD patients.